Sangre iraquí: el devastador costo del petróleo - Samhan, Fabiola (Revista de Estudios Árabes, 2014)
The author emphasizes the ruthless use of weapons by the American army in Iraq, causing civilian and in some cases allied casualties. In an effort to protect its American soldiers, the government offered attractive deals to Latin American citizens to participate in the war effort. The ten years embargo caused terrible human suffering to the Iraqi people, while the devastating firepower destroyed the infrastructure of the country. The effects of the Afghan and Iraqi invasions would, as many predicted, increase hostile activities against the U.S.A. The successive American governments are determined to control energy resources abroad by any means, regardless of dire consequences to targeted countries and their people.